2015
DOI: 10.1002/cctc.201500436
|View full text |Cite
|
Sign up to set email alerts
|

Surface Science Approaches for the Preparation of Alumina‐Supported Hydrotreating Catalysts

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 158 publications
(240 reference statements)
2
34
0
Order By: Relevance
“…The measured hexagonal structure shows a lattice constant between the one of the substrate and the one implied by the bulk oxide. As the overall crystal structure, the structures of the low index surfaces of γ -Al 2 O 3 are still discussed controversially in literature [15,54] and based mostly on theoretical work [55][56][57]. Figure 4 can be best described by subnanometer-sized γ -Al 2 O 3 nuclei.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measured hexagonal structure shows a lattice constant between the one of the substrate and the one implied by the bulk oxide. As the overall crystal structure, the structures of the low index surfaces of γ -Al 2 O 3 are still discussed controversially in literature [15,54] and based mostly on theoretical work [55][56][57]. Figure 4 can be best described by subnanometer-sized γ -Al 2 O 3 nuclei.…”
Section: Methodsmentioning
confidence: 99%
“…Several further metastable phases exist, e.g., γ -, δ-, θ -, χ -, κ-, κ -, and η-Al 2 O 3 [14]. γ -Al 2 O 3 is of special technological importance, as it is the most frequently used catalyst support for hydrotreating [15]. Despite its relevance, the detailed structure of γ -Al 2 O 3 is still under debate [14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface-science type studies can help resolving this issue by using planar surfaces with wellcontrolled surface structure [8]. Specific reactivity of various surface orientations can thus be studied and compared to polycrystalline industrial materials.…”
Section: Introductionmentioning
confidence: 99%
“…These authors claimed that MoS 2 slabs are oriented parallel to the support on the most predominant -Al 2 O 3 (110) surface and show the highest sulfidation degree with respect to the other (100) and (111) orientations. However, the use of thin films epitaxially grown on an oriented substrate as models for -Al 2 O 3 has been questioned [8]. More recently, we showed that -alumina single crystals can be used as a suitable model for -Al 2 O 3 since there are many analogies between the surface structure of -Al 2 O 3 , the metastable polycrystalline industrial support, and -Al 2 O 3 , the thermodynamically stable alumina polymorph from which single crystal wafers can be grown [8,11].…”
Section: Introductionmentioning
confidence: 99%